Transient Expression of a Recombinant Monoclonal Antibody in HEK293T Cells - Omid Mohammadian; Masoumeh Rajabibazl; Hadi Bayat; Azam Rahimpour (Tabriz University of Medical Sciences, 2018)
Background: Monoclonal antibodies (mAbs) are considered the most important and financially successful category of the biopharmaceuticals. Extensive optimization of the expression vector, host system and culture parameters are required for the successful production of active monoclonal antibodies in mammalian cells. In this regards, transient expression enables rapid and cost-effective production of recombinant proteins for initial characterization. Methods: In the present study, an internal ribosome entry site (IRES) based bicistronic expression system has been evaluated for the transient expression of an anti-CD52 monoclonal antibody in mammalian cells. The IRES based bicistronic vector was generated through sequential cloning of the Light chain (LC), IRES, and Heavy chain (HC) in an intermediate vector and transfer of the resulting fragment to the expression vector. Transfection of the HEK293T cells was performed and antibody expression was analyzed in cell culture supernatant. Results: Restriction enzyme analysis indicated successful cloning of the antibody coding unit in the expression vector. Analysis of EGFP expression indicated successful transfection of the HEK293T cells. Production levels of 220 μg/L of antibody were achieved in HEK293T cells during three days of culture. Conclusion: Our results show the convenience and efficiency of the bicistronic expression system for transient expression of the whole monoclonal antibodies in mammalian cells.